2004
DOI: 10.1111/j.0956-7976.2004.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Don't Stand So Close to Me

Abstract: Three studies investigated the effects of self-construal activation on behavior conducive to interpersonal proximity. Study 1 revealed that compared with control participants, participants who were primed with the independent (or personal) self sat further away from where they anticipated another person would sit in a waiting room. Results of Study 2 indicated that participants primed with the interdependent (or social) self sat closer to the anticipated other person than did those primed with the independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 54 publications
(50 reference statements)
1
48
0
Order By: Relevance
“…Previous research has established that this task can effectively prime self-construal (Trafimow et al, 1991; Ybarra and Trafimow, 1998; Holland et al, 2004; Oyserman and Lee, 2008; Lee and Jeyaraj, 2014). Thinking of similarities with close others decreases subjective interpersonal distance, while thinking of differences enhances such distance.…”
Section: Studymentioning
confidence: 99%
“…Previous research has established that this task can effectively prime self-construal (Trafimow et al, 1991; Ybarra and Trafimow, 1998; Holland et al, 2004; Oyserman and Lee, 2008; Lee and Jeyaraj, 2014). Thinking of similarities with close others decreases subjective interpersonal distance, while thinking of differences enhances such distance.…”
Section: Studymentioning
confidence: 99%
“…Obviously, our results reported so far provide no evidence for the assumed underlying process. However, one method commonly used to demonstrate the role of selfconstrual is measuring one's chronic self-construal (e.g., Holland et al 2004, Study 3 [German sample]). In an additional study we used this method to reveal evidence for the assumed process with regard to female decision-makers.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize demand characteristics and self-presentation bias, we measured social affiliation motives using unobtrusive and behavioral measures. First, reasoning that people who are motivated to affiliate should initiate social interactions, we deployed a behavioral measure of physical closeness (adapted from Holland, Roeder, Brandt, & Hannover, 2004). In this behavioral task, physical closeness to another person is used as an indicator of desire for social closeness and as a precursor for any subsequent interaction.…”
Section: Overview Of Researchmentioning
confidence: 99%
“…We used a waiting room task to measure participants’ physical distance/closeness to another (fictitious) participant (adapted from Holland et al, 2004). Research has shown that physical and social distances are conceptually related (Bar-Anan, Liberman, Trope, & Algom, 2007) and that people who are high in affiliation motivation interact physically closer to other people (McAdams & Powers, 1981).…”
Section: Studymentioning
confidence: 99%